PENDEKATAN KOMUNIKATIF DALAM PEMBELAJARAN BAHASA ARAB - Muradi, Ahmad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
The communicative approach in language learning emphasizes on the mastery of language proficiency. Communicative approach is based on some psychological theories of language and learning. The purpose of language learning, according to this approach, is factual communication, where students can use foreign language as a communication tool. In other words, the purpose of this approach is that students have the competence to communicate in a language they have learned in a variety of social situations. Communicative approach is also called the functional approach, in which the language is used as its functions. This article describes the application of communicative approach for teaching Arabic in Indonesian contexts. DOI: 10.15408/a.v1i1.1129